SYNTHESIS OF BIFEO3 AS A FERROELECTRIC MATERIAL BY MEANS OF SONOCHEMICAL METHOD - FIRMAN SIDIQ NIM:10513019, DANI
The synthesis of ferroelectric compound of BiFeO3 by means of sonochemical method was successfully performed by using precursors of Bi5O(OH)9(NO3)4 and Fe(NO3).9H2O with stoichiometric ratio of 1: 1 for Bi3+ and Fe3+ ions. The synthesis process was carried out by dissolving the precursors under acidic conditions at pH = 1 followed by a sonication process for 4 hours with the addition of KOH to achieve pH = 10. The pH of solution was kept to be at pH = 10 during sonication. The resulting solid from sonication then was calcined at 100 °C, 300 °C, 500 °C, 670 °C and 800 °C for 6 hours. Percent yield from the synthesis proces is 97.8%. Based on the X-ray Power Difraction (XRD) data, it showed that BiFeO3 compound was successfully synthesized with secondary phase were also analyzed and identified as Bi2Fe4O9 and Bi25FeO39. It were analyzed Thermogravimetric Analysis (TGA) data showed that BiFeO3 has lost it mass up temperature of 460 °C and stabilized above 460 °C. From the Differential Scanning Calorimetry (DSC) data, it showed that at the temperature of 500 °C, there is a phase transition correlated with the BiFeO3 crystalline formation. The dielectric constants measurements were carried out with frequencies range from 20 Hz to 2 MHz, it showed that there is a transition at 160 oC and correlated with the decreasing of the optical conductivity data. The optical conductivity decreases as temperature increases.